Hubungan mutasi gen ras dan p53 pada penderita karsinoma nasofaring dengan riwayat merokok - Mohammad Dwijo Murdiyo; Cici Sunihapsari; Pudji Rahaju; Endang Retnoningsih; Johanes Bambang Soemantri (Oto Rhino Laryngologica Indonesiana, 2013)
Background: Nasopharyngeal carcinoma (NPC) is a malignancy with multifactorial etiology involving Epstein Barr virus infection, genetic and environmental factors. Cigarette smoking is one of the environmental factors which have many compounds of carcinogen. Oncogene ras and tumor suppressor p53 gene play an important role in carcinogenesis. Mutation of these genes may contribute to NPC carcinogenesis. Purpose: To determine correlation between ras and p53 mutations in NPC patients with cigarette smoking history (quantity, duration, cumulative exposure). Methods: Thirty patients diagnosed as end stage type III WHO NPC were included in this cross sectional study. Thirty NPC biopsies were assessed for ras and p53 mutation by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). The Fisher’s exact test and T test were used to analyse the correlation of ras, p53 mutation and cigarette smoking history. Results: Nras mutation was observed in 21(75%) subjects. One (3,33%) subject had H-ras mutation. There were no significant correlation between cigarette smoking history with N-ras (p=0,662) and H-ras (p=0,400) mutation, no significant correlation between N-ras, H-ras mutation with quantity, duration and cumulative exposure ofcigarette smoking (p>0.05). The p53 mutation was observed in 27 (93.1%). No significant correlation between cigarette smoking history and p53 mutation (p=1.000). No significant correlation between p53 mutation with quantity, duration and cumulative exposure of cigarette smoking (p>0.05). Conclusion: There were no significant correlation between cigarette smoking history and mutation of N-ras, H-ras and p53. N-ras, H-ras, p53 mutations were not correlated with quantity, duration and cumulative exposure of cigarette smoking.Keywords: nasopharyngeal carcinoma, ras, p53, cigarette smoking. ABSTRAKLatar belakang: Karsinoma nasofaring (KNF) memiliki etiologi multifaktorial yaitu infeksi virus EpsteinBarr, faktor genetik dan faktor lingkungan. Asap rokok adalah salah satu faktor lingkungan yang mengandungbahan karsinogen. Onkogen ras dan tumor suppressor gen p53 memiliki peran pada karsinogenesis. Mutasi gengentersebut dianggap berperan pada karsinogenesis KNF. Tujuan: Untuk mengetahui hubungan mutasi gen rasdan p53 pada penderita KNF dengan riwayat merokok. Metode: Studi cross sectional dengan subjek penelitian 30penderita KNF WHO tipe III stadium lanjut. Pemeriksaan mutasi gen ras dan p53 melalui pemeriksaan polymerasechain reaction (PCR) dan restriction fragment length polymorphism (RFLP). Analisa statistik menggunakan ujiFisher’s exact dan uji T. Hasil: Mutasi N-ras didapatkan pada 21(75%) subjek dari 28 subjek yang dapat diketahuimutasinya. Satu (3.33%) subjek mengalami mutasi H-ras dari 30 subjek. Tidak didapatkan hubungan bermaknaantara mutasi N-ras (p=0.662) dan H-ras (p=0.400) dengan riwayat merokok. Tidak ada perbedaan bermakna rataratajumlah, lamanya dan paparan kumulatif rokok antara subjek yang mengalami mutasi atau tidak mutasi N-rasdan H-ras (p>0,05). Mutasi p53 didapatkan pada 27 (93.15%) subjek dari 29 subjek. Tidak ada hubungan bermaknaantara riwayat merokok dengan terjadinya mutasi p53 (p=1.000). Tidak ada perbedaan bermakna rata-rata jumlah,lamanya dan paparan kumulatif rokok antara subjek yang mengalami mutasi atau tidak ada mutasi p53 (p>0,05).Kesimpulan: Tidak didapatkan hubungan bermakna antara riwayat merokok dengan terjadinya mutasi N-ras, Hrasdan p53. Tidak ada perbedaan bermakna rata-rata jumlah, lamanya dan paparan kumulatif rokok antara subjekyang mengalami dan yang tidak mengalami mutasi N-ras, H-ras dan p53.Kata kunci: karsinoma nasofaring, ras, p53, merokok.